Effects of Patient-Controlled Epidural Analgesia and Patient-Controlled Intravenous Analgesia on Analgesia in Patients Undergoing Spinal Fusion Surgery. (November 2016) - Li, Yong; Lu, Shan; Ma, Si-Chao; Fan, Hong-Wu; Zhao, Guo-Qing
Abstract : We compared the outcomes of patient-controlled epidural analgesia (PCEA) and patient-controlled intravenous analgesia (PCIA) in analgesia after spinal fusion surgery. A total of 120 patients who underwent spinal fusion surgeries between April 2013 and April 2015 at Shaanxi Provincial People's Hospital were selected for this study based on defined inclusion criteria. All patients were randomly divided into 2 groups before surgery: PCEA group (n = 65) and PCIA group (n = 55). Visual analog scales (VAS) were used to evaluate the degree of pain. Besides, the active and passive activities of patients during 1- to 3-day recovery period after surgery were recorded. Verbal rating scales were used to measure pain levels after surgery and after surgery. Adverse effects of PCEA and PCIA were monitored, which included nausea, vomiting, pruritus, drowsiness, respiratory depression, and headache. Our results showed no statistically significant differences between PCEA and PCIA in sex ratio, age, height, weight, American Society of Anesthesiologists level, surgery time, number of fusion section, surgery methods, and duration of anesthesia (all P > 0.05). The PCEA group was associated with significantly lower VAS scores, compared with the PCIA group, at 3, 6, 12, 24, and 48-hour postsurgery (all P < 0.05) when surgery-associated pain is expected to be intense. Also, compared with the PCIA group, the PCEA group showed higher frequency of recovery activities on first and second day postsurgery (all P < 0.05). The overall patient satisfaction level of analgesia in the PCEA group was significantly higher than in the PCIA group ( P < 0.05). Moreover, the incidence of hypopiesia and skin itching in the PCIA group was higher than in the PCEA group (all P < 0.05). Finally, drowsiness and headache were markedly lower in the PCIA group after surgery, compared with the PCEA group, and this difference was statistically significant (all P < 0.05). Our results provide strong evidence that PCEA exhibits significantly greater efficacy than PCIA for pain management after spinal fusion surgery, with lower VAS scores, higher frequency of recovery activities, and overall higher satisfaction level.